Extraction and characterization of nanocellulose from sugarcane bagasse by ball-milling-assisted acid hydrolysis - Kittiya Plermjai; Kanokthip Boonyarattanakalin; Wanichaya Mekprasart; Sorapong Pavasupree; Weerachon Phoohinkong; Wisanu Pecharapa (My University, 2018)
This study is proposed to characterize nanocellulose extracted from sugarcane bagasse (SCB). For extracting cellulose, the bagasse was treated by chemical treatment. The nanocellulose was prepared using ball-milling with acid hydrolysis. Morphology of bagasse, cellulose and nanocellulose were characterized by scanning electron microscopy (SEM). The chemical composition of extracted cellulose and nanocellulose was investigated by Fourier-transformed infrared spectroscopy that verifying the removal of lignin and hemicellulose during cellulose isolation process from sugarcane bagasse. The crystalline structure of cellulose and nanocellulose were characterized by X-ray diffraction (XRD), indicating that the nanocellulose prepared by ball milling with acid hydrolysis has higher crystallinity than nanocellulose prepared only ball milling.
Keywords: Nanocellulose; Bagasse; Hemicellulose; Advanced Cellulose Research Studies